Carbon sequestration and enhanced hydrocarbon recovery: ultrasonics Vp and Vs and laboratory fluid replacement for the Mississippian carbonates, Wellington field, Kansas - King, Matilda Awo (My University, 2025)
The feasibility of enhanced oil recovery (EOR) and carbon geosequestration for the Mississippian carbonates of south-central Kansas remains an important endeavor. This depleting reservoir formation has heterogeneous lithofacies, variable pore structures, and potentially pore-fluid composition of variable seismic signatures. Understanding the elastic properties of these carbonates is crucial for assessing their reservoir qualities through optimizing fluid injection strategies and conducting insightful seismic modeling. This study employs ultrasonic velocity measurements to investigate the elastic moduli of Mississippian carbonates, understand the response of P- and S-waves to pore fluid changes, and contribute assessing the suitability of these formations for long-term CO₂ storage and EOR programs. An ultrasonic laboratory system was used to measure compressional (P-wave) and shear (S-wave) velocities under both dry and fluid-saturated conditions, while porosity was determined using a porosimeter. Additionally, fluid substitution modeling was performed to analyze how different pore fluids influence wave propagation. The results indicate that traditional velocity analysis alone may not be sufficient for fluid discrimination in reservoirs. Instead, attenuation measurements proved to be a more reliable attribute for distinguishing between pore fluids, highlighting its potential application in monitoring reservoir conditions during EOR operations. These findings suggest that attenuation-based analyses could improve the identification of dry reservoirs and enhance the detection of fluid migration during injection processes. Furthermore, the favorable elastic properties of the Mississippian carbonates, including their ability to retain mechanical integrity under varying saturation conditions, support their viability as candidates for both hydrocarbon recovery and CO₂ sequestration. This research provides valuable insights into the geophysical characterization of carbonate reservoirs and contributes to the development of more effective strategies for sustainable energy production and carbon storage. This research resulted in establishing an approach to estimate in-situ shear wave velocity based on laboratory ultrasonic Vp and Vs and sonic Vp well-log data, thus paving the way for a data driven technique of estimating in-situ Vs , when only sonic Vp is available.
Keywords: Carbon sequestration; Enhanced oil recovery; Wellington field; Mississippian carbonates; Attenuation and dispersion; P-wave and S-wave velocities